2001
DOI: 10.1002/chin.200118252
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Application of Radical Cage Reactions in Studies of Microstructures of Polymers and Composites

Abstract: Application of Radical Cage Reactions in Studies of Microstructures of Polymers and Composites -[103 refs.]. -(DAVYDOV, E. YA.; VOROTNIKOV, A. P.; PUSTOSHNYI, V. P.; PARIISKII, G. B.; Russ. Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…74 This leads to a higher concentration of diazo compounds in the regions with a decreased packing density of macromolecules, which can result in the formation of clusters. Thus EPR spectroscopy revealed that photolysis (at 77 K) of DDM in common and perdeuterated PMMA, PS and polycarbonate (PC) resulted in carbenes Ph 2 C: formed in the matrix-isolated state and also biradicals 1 75,76 generated in the regions with a decreased packing density of macromolecules due to conversion of DPC dimers (2) in clusters according to the scheme The EPR spectrum of biradicals generated in reaction ( 13) is shown in Fig. 3 a.…”
Section: Determination Of Molecular-dynamic Characteristics Of Polyme...mentioning
confidence: 99%
See 4 more Smart Citations
“…74 This leads to a higher concentration of diazo compounds in the regions with a decreased packing density of macromolecules, which can result in the formation of clusters. Thus EPR spectroscopy revealed that photolysis (at 77 K) of DDM in common and perdeuterated PMMA, PS and polycarbonate (PC) resulted in carbenes Ph 2 C: formed in the matrix-isolated state and also biradicals 1 75,76 generated in the regions with a decreased packing density of macromolecules due to conversion of DPC dimers (2) in clusters according to the scheme The EPR spectrum of biradicals generated in reaction ( 13) is shown in Fig. 3 a.…”
Section: Determination Of Molecular-dynamic Characteristics Of Polyme...mentioning
confidence: 99%
“…Thus, the effective potential barrier decreases as the temperature increases, and the rate of the process increases accordingly. Vorotnikov et al 61,66,67 determined the values of parameters for the tunnelling of H atom to CHC and DPC in the same polypiperylene matrix. The height U and the width x of the potential barrier as well as the equilibrium distance (R 0 ) between carbon atoms of the active centre of carbene and the C7H groups of polypiperylene in the carbene ± polypiperylene complex were determined from the kinetic data obtained at 77 ± 133 K. The boundary values of these parameters, which correspond to the maximum and minimum rate constants of carbene decay, are presented in Table 1.…”
Section: The Effect Of Spatial Orientation Factors On the Decay Kinet...mentioning
confidence: 99%
See 3 more Smart Citations